Advancements in Müller Glia Reprogramming: Pioneering Approaches for Retinal Neuron Regeneration - Yuyan Zhou; Song Qin; Haixiang Wu (Neuroglia)
Müller glia exhibit a remarkable regenerative capacity in zebrafish through spontaneous reprogramming post-injury but remain limited in mammals. This review highlights the key mechanisms underlying Müller glia reprogramming, including gene regulatory networks, cytokine signaling, signal transduction pathways, epigenetic modifications, and transcriptional regulation. Cross-species analyses have uncovered conserved gene networks that suppress neurogenesis in mammals, while injury-induced transcriptional profiles reveal divergent regenerative strategies. Combinatorial approaches may enhance the reprogramming of mammalian Müller glia into functional neurons. Nevertheless, significant challenges remain, such as variability in the efficacy of direct reprogramming methods and the limited regeneration of cone photoreceptors, even in regenerative species. We conclude that targeting epigenetic barriers and species-specific regulatory pathways offers promising avenues for clinical translation in retinal disorders such as glaucoma and retinitis pigmentosa. Moving forward, research efforts should prioritize the functional integration of regenerated neurons and the development of standardized methodologies to accelerate therapeutic advancements.